Strategi Penguatan Perempuan dalam Pembangunan Perekonomian Subsektor Perikanan Aceh (Studi Kasus Agroindustri Perikanan di Desa Meunasah Keudee Kecamatan Mesjid Raya Kabupaten Aceh Besar) - Safrida Safrida; Agussabti Agussabti; Sofyan Sofyan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. After Tsunami 2004, many local and international NGOs came to help Aceh community in rehabilitation and reconstruction processes in order to relief economic condition of the community. In the rehabilitation processes of coast community, NGO gave more attention to gender equity in their program, especially in the program aimed to increase knowledge and skill through the training of small scale enterprise and giving fund for their business. In 2010, the rehabilitation and reconstruction processed was finished. How is the women role in economic sector? This research aimed to: (1) Describe the women role in fishery subsector before and after tsunami, (2) Analyze factors which caused the change of woman role in fishery subsector after tsunami, (3) Formulate the strategy to reinforce woman role in economic activity of fishery subsector. This research was a case study in Meunasah Keudee Village, Mesjid Raya Subdistrict, Aceh Besar District by using a qualitative approach. The results showed that there were a movement in a role of men and women in fishery agroindustry. Many factors caused this movement: internal factors which are: (a) the increasing awareness of self potential, (b) the increasing of cosmopolitness in women activity after tsunami, (c) the movement of status and women role in their family (widows case); external factors which are: (a) NGOs assistances and guidances in women economic activity, (b) the increasement of family needs, (c) the movement of reference group. Strategy to enhance women role are: (1) increasement of women education through training which includes gender issues in economic assitances to the community; (2) reformation of local or traditional institution which neglect women role; (3) advocate the men to give the same place and role to the women to involve on desicion making processes in the family, economic activity and public sphere.